The Description of a Crowdfunding Project and Potential Donors’ Willingness to Donate - Awdziej, Marcin; Tkaczyk, Jolanta; Krzyżanowska, Jolanta (Studia Oeconomica Posnaniensia, 2018)
The aim of the article is to identify how the description of a crowdfunding project affects potential donors’ willingness to fund a project. The authors attempted to answer two research questions: 1. Does donors’ willingness to support a project depend on its communication style? 2. What is the relationship between a project’s description and the size of the donation? Considering the research questions and the context the authors conducted the study in two stages. In the first stage netnography was chosen as a research method, in the second, a laboratory experiment encompassing 156 students. Students were randomly assigned to one of four experimental groups. These groups were diversified by the type of project (hedonic and utilitarian) and the communication style (market and product style). The communication style used in the project description has influence on neither the willingness to support such projects nor the donated amounts.